Enhancing mechanical strength of carbon fiber-epoxy interface through electrowetting of fiber surface. (1st April 2022) - Chen, Xiaoming; Wen, Kaiqiang; Wang, Chunjiang; Cheng, Siyi; Wang, Shuo; Ma, Hechuan; Tian, Hongmiao; Zhang, Jie; Li, Xiangming; Shao, Jinyou
Abstract: The interfacial shear strength between carbon fiber and polymer matrices plays a critical role in bulk mechanical performances of carbon fiber-reinforced polymer composites. However, finding simple and effective methods for modulating the interfacial adhesion remains challenging even after over a decade of research and development. Herein, a novel method based on electrically-assisted wetting technique was developed to strengthen the interfacial adhesion between carbon fiber and polymer matrix. The results indicated the polymer completely infiltrated the small grooves on the fiber surface under applied external electric field during the curing process, leading to the formation of conformal contact interface. The interfacial properties were characterized by utilizing the microdroplet debonding and single fiber fragmentation tests. It is found that the as-prepared composites exhibit a maximum increased interfacial shear strength (IFSS) reaching up to 119.69 MPa, a value 81.02% higher than that of the original fiber-based composites. The reinforcement mechanism was ascribed to the improved wettability and mechanical interlock effect induced by the applied electrical stimulus which was supported by dynamic simulation of two-phase flow. In sum, the suggested simple, facile, and environmentally friendly strategy can effectively regulate the interfacial load transfer capacity, thereby suitable for the optimal design of fiber-reinforced composites. Graphical abstract: Image 1 Highlights: A green, and economical electrically-assisted wetting method is proposed to improve the interfacial properties. Electrically-assisted wetting promotes preferable resin wetting and formation of mechanical interlocking. The two-phase flow dynamic simulation reveals the rheological behaviors of the resin and the reinforcement mechanism. The proposed method will not cause damage to the fiber and is compatible with other modification methods.